Economic Analysis of New Single-Inhaler Triple Therapies in Patients with COPD in the UK - Cai R; Martin AA; Ge Y; Risebrough NA; Haeussler K; Compton C; Halpin DM; Ismaila AS (International Journal of COPD)
Rui Cai,1 Alan A Martin,2 Yuchen Ge,3 Nancy A Risebrough,3 Katrin Haeussler,4 Christopher Compton,5 David MG Halpin,6 Afisi S Ismaila7,8 1ICON Health Economics, ICON plc, Amsterdam, the Netherlands; 2Value Evidence and Outcomes, GSK, London, UK; 3ICON Health Economics, ICON plc, Toronto, ON, Canada; 4ICON Health Economics, ICON plc, Munich, Germany; 5Global Medical, GSK, London, UK; 6University of Exeter Medical School, College of Medicine and Health, University of Exeter, Exeter, UK; 7Value Evidence and Outcomes, GSK, Collegeville, PA, USA; 8Department of Health Research Methods, Evidence, and Impact, McMaster University, Hamilton, ON, CanadaCorrespondence: Afisi S Ismaila, Value Evidence and Outcomes, GSK, 1250 South Collegeville Road, Collegeville, PA, 19426-0989, USA, Tel +19193158229, Email afisi.s.ismaila@gsk.comPurpose: Chronic obstructive pulmonary disease (COPD) is associated with a substantial economic burden in the UK. Although previous analyses have compared the cost-effectiveness of single-inhaler triple therapy (SITT) versus dual therapy or multiple-inhaler triple therapy, there are no studies investigating the cost-effectiveness of individual SITTs versus other SITTs. This study assessed the cost-effectiveness of SITT with fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) versus other SITTs for the treatment of COPD from a UK National Health Service perspective.Patients and Methods: The validated GALAXY-COPD model was populated with patient baseline characteristics from the IMPACT study and treatment effect data from a network meta-analysis, which compared FF/UMEC/VI with budesonide/glycopyrrolate/formoterol fumarate (BUD/GLY/FOR; both 320 μg and 160 μg dosing; BUD320 and BUD160, respectively) and beclometasone dipropionate/formoterol fumarate/glycopyrrolate (BDP/FOR/GLY). UK healthcare resource unit and drug costs (Great British Pound, 2022) were applied, with costs and outcomes (except life years [LYs]) discounted at 3.5% annually. The base case was probabilistic (5000 iterations) with a lifetime horizon.Results: FF/UMEC/VI provided an additional 0.620 (95% range: 0.255, 1.025) LYs and 0.283 (0.080, 0.501) quality-adjusted LYs (QALYs) with a cost saving of £ 1620 (£ 158, £ 3243) versus BUD320/GLY/FOR, an additional 0.627 (0.261, 1.053) LYs and 0.309 (0.097, 0.533) QALYs at a cost saving of £ 1721 (£ 261, £ 3345) versus BUD160/GLY/FOR, and an additional 0.328 (0.063, 0.654) LYs and 0.230 (0.035, 0.437) QALYs at a cost saving of £ 1221 (−£ 541, £ 2796) versus BDP/FOR/GLY. FF/UMEC/VI was less costly and showed higher QALYs in 98.2%, 98.9%, and 93.6% of simulations versus BUD360/GLY/FOR, BUD160/GLY/FOR, and BDP/FOR/GLY, respectively. At a willingness-to-pay threshold of £ 20,000 per QALY, the probability of FF/UMEC/VI being cost-effective was 99.9%, 100%, and 99.3% versus BUD320/GLY/FOR, BUD160/GLY/FOR, and BDP/FOR/GLY, respectively.Conclusion: Based on this analysis, FF/UMEC/VI is a dominant (improved outcomes with cost savings) treatment option compared with other SITTs for the treatment of patients with COPD in the UK.Keywords: chronic obstructive pulmonary disease, cost-effectiveness, fluticasone furoate/umeclidinium/vilanterol, GALAXY model, probabilistic